The Relevance of K.H. Maimun Zubair’s Concept of Nusantara Islamic Education to the Indonesian Education System - Supriaji, Ujud; Nasution, Khoiruddin; Hasyim, A. Dardiri (Edumaspul: Jurnal Pendidikan, 2026)
This study examines the relevance of K.H. Maimun Zubair’s concept of Nusantara Islamic education to the contemporary Indonesian education system. Nusantara Islam represents an approach to Islamic education that integrates classical Islamic scholarship, local cultural wisdom, and national values. This research employs a qualitative descriptive method based on document analysis and in-depth interviews as secondary support. The findings indicate that K.H. Maimun Zubair’s educational thought is constructed upon three main pillars: mastery of classical Islamic knowledge, integration of nationalism and religious commitment, and emphasis on moral character and exemplary conduct. These principles correspond with current educational priorities in Indonesia, particularly in strengthening character education, promoting religious moderation, and fostering social harmony. The study further reveals that the relevance of this concept lies in its potential contribution to reducing ideological polarization and reinforcing inclusive religious attitudes among students. This research concludes that the educational model developed by K.H. Maimun Zubair offers a contextual and culturally grounded framework that can enrich national education policies and practices in Indonesia.